The Law of Forensics: a proof beyond the shadow of doubt - Lubogo, Isaac Christopher (Jescho Publishing House, 2021)
This book gives an understanding of the application of forensic sciences to the law. It covers the crime scene investigation process, and provides an overview of the various kinds of forensic evidence that may be collected and presented in court. Points out the identification, documentation and collection of physical evidence, including fingerprints, shoe impressions, hair fibers, firearms evidence and questioned documents, It considers biological evidence, including DNA, and tries to analyse the scientific unimpeachablity of DNA, blood spatter and other fluids, forensic anthropology and odontology. Finally, the book engages fire investigation and forensic accounting. It is designed to provide a foundation in the field of criminology who are interested in the use of science and law to solve crime, and considers the impact of television and other media on the field of Forensic Science and the courtroom.
Keywords: Forensics - Legal aspects; Forensic science - Legal aspects